Arterial Stiffness and Vitamin D Levels: the Baltimore Longitudinal Study of Aging - Giallauria, Francesco (Endocrine Society, 2012)
CONTEXT: The importance of vitamin D for bone health has long been acknowledged. Recent evidence suggests that vitamin D can also play a role in reducing the risk of several other diseases, including cardiovascular disease. OBJECTIVE: The aim of this study is to test the hypothesis that 25-hydroxyvitamin D (25-OH D) is an independent cross-sectional correlate of central arterial stiffness in a normative aging study population. DESIGN AND SETTINGS: We conducted a cross-sectional analysis. SUBJECTS: We studied 1228 healthy volunteers (50% males; age, 70 ± 12 yr) of the Baltimore Longitudinal Study of Aging. MAIN OUTCOME MEASURES: We measured carotid-femoral pulse wave velocity (PWV) and 25-OH D levels. RESULTS: We found a significant inverse association between PWV and 25-OH D levels (adjusted r(2) = 0.27; β = −0.43; P = 0.001). After adjusting for age, gender, ethnicity, season of blood draw, estimated glomerular filtration rate, physical activity level, cardiovascular risk factors score (smoking, visceral obesity, hypercholesterolemia, hypertension, and diabetes), calcium/vitamin D supplementation, serum calcium, and PTH levels, the association between PWV and 25-OH D levels was only slightly reduced and remained statistically significant (adjusted r(2) = 0.34; β = −0.34; P = 0.04). CONCLUSIONS: Vitamin D levels are inversely associated with increased arterial stiffness in a normative aging population, irrespective of traditional risk factor burden. Further research is needed to understand the mechanism of this association and to test the hypothesis that vitamin D supplementation can reduce arterial stiffness.